Changes in electrical response function and myosin heavy chain isoforms following denervation and reinnervation of bilateral posterior cricoarytenoid muscles in dogs. (March 2014) - Li, Jingyuan; Liu, Shaofeng; Cheng, Qiuhui; Nie, Mingrong; Zhang, Siyi; Sheng, Xiaoli; Chen, Shaohua; Ge, Pingjiang
Abstract Conclusions: Both electrical response function and mRNA expression of myosin heavy chain (MyHC) types 2X, 1, and Neonatal of bilateral posterior cricoarytenoid (PCA) muscle changed after denervation or reinnervation in canines. Objectives: There is a need to investigate the electrical response function MyHC alteration of denervation or reinnervation in the bilateral PCA muscle of large animals. Methods: MyHC isoforms expression profile and PCA muscle function outcome were detected by real-time reverse transcribed-polymerase chain reaction and muscle response to functional electrical stimulation, 9 weeks after denervation and reinnervation with ansa–recurrent laryngeal nerve anastomosis in dogs. Results: Denervation produced up-regulation of MyHC-1 and MyHC-Neonatal messenger ribonucleic acid (mRNA) expression. Reinnervation caused a decrease of MyHC-2X mRNA expression. The electrical voltage threshold of vocal fold movement and maximum abduction of denervation were greater than that of the reinnervated or control group. The denervated vocal abduction maximum of response to electrical stimulation was less than that in reinnervation or control groups.